LA PRUEBA PERICIAL - Ramón Ruffner de Vega, Jeri Gloria (2014)
The present article aims to present some aspects regarding of expert evidence in the Code of Civil and Peruvian Criminal Procedure Code.At the present, the administrator of justice often requi-res input that certain matters can offer a specialist on the subject, on any scientific or technical knowledge, to clarify the truth, through the expert, who through the application of science, trade or occupation, experience or the use of technical tests will determine the veracity of the material points of dispute about a particular event, expert evidence is a form of evidence where the judge finds its greatest degree of conviction.